Financial relief policy and social distancing during the COVID-19 pandemic - Cody Yu-Ling Hsiao; Stanley Iat-Meng Ko; Nan Zhou (Public Library of Science (PLoS), 2022)
In this paper, we investigate the effect of stimulus payments during the COVID-19 pandemic on the social distancing practices of their recipients. While the directed cash payments stipulated by the 2020 CARES Act were intended to mitigate the economic impact of closures imposed in response to the outbreak, we find that this relief may also have inadvertently contributed to the spread of the virus due to increased social activity. We find that, as the payments were sent out on a staggered weekly schedule, there was a corresponding spike in weekend traffic as indicated by a number of mobility metrics that measure social distancing, over and above the usual uptick expected from weekend shopping following receipt of the stimulus payments on Fridays. This preliminary study gives some indication that the economic benefits of the stimulus package may in fact be outweighed by the detrimental effects of looser social distancing practices prolonging the outbreak.